Selection of a new peptide homing SK-BR-3 breast cancer cells - Pereira, Ana Cláudia Santos (2020)
Breast cancer diagnosis remains a challenge, mostly due to its heterogeneity. This reality translates in delayed treatments, increasing treatment aggressiveness and lower chances of overall survival. The conventional detection techniques, although becoming increasingly sophisticated each year, still lack the ability to provide reliable conclusions without being time consuming, expensive and uncomfortable for the patients. The identification of novel biomarkers for breast cancer research is therefore of utmost relevance for an early diagnosis. Moreover, breast cancer specific peptide moieties can be used to develop novel targeted drug delivery systems. In this work we used phage display to identify a novel peptide with specificity to the SK-BR-3 breast cancer cell line. Cytometry assays confirmed its specificity, while bioinformatics and docking studies predicted the potential biomarkers at the SK-BR-3 cells surface. These findings can be potentially useful in the clinical context, contributing to more specific and targeted therapeutic solutions against HER2-positive breast cancer subtypes.